Conventional Twin-Block Versus Cervical Headgear and Twin-Block Combination: Therapeutic Effects on the Craniofacial Structures in Growing Subjects - Beytullah Gülsoy; Mehmet Ali Yavan (Galenos Yayinevi, 2023)
Objective:To compare the short-term effects of the conventional twin-block (TB) appliance and the cervical headgear TB (CHG-TB) appliance on craniofacial structures.Methods:The retrospective controlled study examined lateral cephalograms taken from 46 growing subjects. Individuals were divided into two groups according to the treatment. Group I consisted of 15 individuals (9 girls, 6 boys, mean age: 12.34±1.23 years) treated with the TB appliance and Group II consisted of 16 individuals (9 girls, 7 boys) treated with the CHG-TB appliance (mean age: 12.50±1.30 years). To distinguish the treatment effects of these appliances on growth, a control group of 15 untreated individuals (9 girls, 6 boys, mean age: 11.82±1.16 years) was included from the archives.Results:Significant improvements were found in the interdental and maxillo-mandibular measurements in the treatment groups (p<0.001). Significant differences were observed in the SNA, SN/PP, and SN/GoGn values in the CHG-TB group compared to other groups (p<0.05). The mandible showed a significant downward movement in both treatment groups compared with the control group (p<0.001), while the change in SNB angle was statistically significant only in the TB group compared to the control group (p<0.05). Lower incisors showed significant proclination only in the TB group (p<0.05).Conclusion:The CHG-TB appliance was found to be more effective in limiting maxillary growth and preventing lower incisor proclination compared with the TB appliance, whereas the TB appliance was more effective in anterior mandibular movement.